Accounting for Intangible Assets: Use of Relevant Accounting Standards - Islam, Md. Aminul (Asian Accounting and Auditing Advancement, 2013)
Accounting practices of intangible assets like goodwill, patent, copyright, trademark, research, and development differ from country to country. In Australia, Belgium, Brazil Canada, France, Germany, Sweden, USA, Japan, and the Netherlands, systematic amortization is found. The period of amortization varies from 5 to 40 yrs. In Hong Kong, Mexico, Nigeria, Italy, the UK, and EC immediate write-off is more popular. In Switzerland no amortization is preferable. IAS and BAS provide that purchased goodwill may be amortized within 40 years but internally generated goodwill should not be amortized. Because there might be a subjective valuation of the market value of assets.